Answer:
[tex]-125a^{11}[/tex]
Step-by-step explanation:
The expression that we have in this problem is
[tex](-5a^2)^3\cdot a^5[/tex]
First of all, we proceed by evaluating the power of the term in the brackets. We apply the rule:
[tex](a^m)^n=a^{m\cdot n}[/tex]
So
[tex](a^2)^3=a^6[/tex]
Moreover, we have
[tex](-5)^3=-125[/tex]
Therefore,
[tex](-5a^2)^3=-125 a^6[/tex]
So now the expression is
[tex]-125a^6 \cdot a^5[/tex]
Now we apply the following rule:
[tex]a^m \cdot a^n = a^{m+n}[/tex]
So we have
[tex]a^6\cdot a^5 = a^{6+5}=a^{11}[/tex]
Therefore, our expression becomes:
[tex]-125a^6\cdot a^5=-125a^{11}[/tex]